Boundary-Aware Prototype in Semi-Supervised Medical Image Segmentation - Wang, YongChao (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2024)
The true label plays an important role in semi-supervised medical image segmentation (SSMIS) because it can provide the most accurate supervision information when the label is limited. The popular SSMIS method trains labeled and unlabeled data separately, and the unlabeled data cannot be directly supervised by the true label. This limits the contribution of labels to model training. Is there an interactive mechanism that can break the separation between two types of data training to maximize the utilization of true labels? Inspired by this, we propose a novel consistency learning framework based on the non-parametric distance metric of boundary-aware prototypes to alleviate this problem. This method combines CNN-based linear classification and nearest neighbor-based non-parametric classification into one framework, encouraging the two segmentation paradigms to have similar predictions for the same input. More importantly, the prototype can be clustered from both labeled and unlabeled data features so that it can be seen as a bridge for interactive training between labeled and unlabeled data. When the prototype-based prediction is supervised by the true label, the supervisory signal can simultaneously affect the feature extraction process of both data. In addition, boundary-aware prototypes can explicitly model the differences in boundaries and centers of adjacent categories, so pixel-prototype contrastive learning is introduced to further improve the discriminability of features and make them more suitable for non-parametric distance measurement. Experiments show that although our method uses a modified lightweight UNet as the backbone, it outperforms the comparison method using a 3D VNet with more parameters